Carrots or sticks? Inferring motives of corporate CSR Engagement from empirical data - Peter Kotzian (Review of Managerial Science, 2022)
What drives Corporate Social Responsibility (CSR) engagement of firms? Most empirical literature on firms' CSR engagement focuses on benefits resulting from CSR engagement which are granted by the public. Other studies argue that firms are driven by fear of negative public reactions. This raises, firstly, the question, whether rewards or punishments drive CSR engagement of firms. Secondly, how can we find out, whether benefits or punishments are more relevant? This study starts out from the observation that CSR is defined by going beyond statutory prescriptions monitored and enforced by legal institutions. Existing literature argues that firms orient themselves at public expectations regarding CSR, which are presumed to increase over time. But the specific drivers and mechanisms of this increase are yet unclear. Based on simple behavioral assumptions, we derive developments of CSR engagement for the overall population of firms and sub-populations. These developments differ in crucial aspects, depending on whether firms engage in CSR because they expect benefits or punishments. Comparing empirical data on CSR engagement at the population and sub-group level from different economic regions with implications derived from the behavioral assumptions indicates that in the US, the public exercises pressure by imposing punishments rather than by offering rewards, while this is not the case in other economic regions.
Keywords: 650; Corporate social responsibility; CSR; Social Constructivism; ESG performance